The Investigation According to Some Variables of COVID-19 Fear Levels of High School Students in the Pandemic Process - Editor, Sıtkı Özbek; Hüseyin Nasip Özaltaş, (Journal of Educational Issues, 2024)
The aim of this study was to examine the COVID-19 fear of high school students in the COVID-19 pandemic proccess, based on a few characteristics. Within the scope of this aim, the study’s research group; in the 2020-2021 academic year, a total of 760 students, 382 girls and 378 boys, were identified using a sample technique that can be readily located among high school students who continue their studies in Krşehir province. In the research, for determining the COVID-19 fear levels of students, Ahorsu et al. (2020), and Bakioğlu et al. (2020) “COVID-19 Fear Scale” adapted into Turkish was used. Kolmogorov-Smirnowa values showed that the data were normally distributed. Frequency and percentage analyzes were applied in descriptive statistics, T test was used in the analysis of binary groups, and One way Anova was used in the analysis of three or more groups. As a result of these analyzes, it was determined that the high school students participating in the study had a moderate (x̄ = 15.7) fear of COVID-19. It was determined that the COVID-19 fear levels of high school students the pandemic process, according to the gender variable, the COVID-19 fears of female students (x̄ = 17.26) were significantly higher than male students (x̄ = 14.21). Yet, it was determined that the variables of age, class, being in the school team, doing licensed sports, type of sports, duration of doing sports and getting COVID-19 disease did not have a significant effect on high school students’ fear of COVID-19. As a conclusion, it was shown that fear of COVID-19 in high school students created substantial disparities in favor of girls only on the basis of gender. Other characteristics revealed in the study had no significant effect on high school students’ COVID-19 fear levels.